Agriculture abandonment, land-use change and fire hazard in mountain landscapes in Northeastern Portugal - Azevedo, João (2010)
In this study we analysed changes in pattern and process in a Mediterranean mountain landscape, the França parish, Portugal, over a 47-year period of time. We quantified changes in composition and configuration based on land use/land cover data obtained from 1958, 1968, 1980, 1993, and 2005 aerial photography. For the same period we studied changes in fire, a relevant ecological disturbance in the region and sensitive to change in land use/land cover pattern, through fire behaviour modelling and simulation with FlamMap and FARSITE. The results showed that the study landscape went through relevant modifications over the past 47 years. Agriculture land was replaced by shrublands and forests decreasing progressively from 22% of the landscape in 1958 to less than 5% in 2005,. Shrublands were the dominant land use in all the dates. Structurally, there was an increase in patch size for the most combustible land classes (shrublands and forests) as well as in connectivity for the same classes. Fire simulations indicated that as landscape structure changed over time there were also changes in fire behaviour parameters: increase in fire intensity in the landscape level and average burned area. There was, however, a decrease in average burned area for 4-hr fires from 1993 to 2005 and a decrease in the rate of growth of the highest fireline intensity class (EXTREME). This study showed that changes caused by human abandonment affected the structure of a mountain area in the Northeast of Portugal which enhanced landscape conditions for the occurrence of larger and more intense fire events over time.